How to Read Annual Report and Balance Sheet: A comprehensive guide to understanding annual reports and financial statements (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In any company, there are many departments, which perform many operational activities to reach organizational objective. The performance of these departments may or may not be mutually dependent, but at the ending they are related together by one common thread – Accounting Finance department. The aspects of every department are recorded and reported to various stakeholders. The Reporting involve the disclosure of financial information about financial position of the business. Companies are evaluated and decisions are made on the basis of opinion arrive at on scrutinising the annual report and financial statement. Deals are clinched and opinion are win on quote information read and data procured from the annual report and yet ,there is a lack of knowledge of financial statement-an ignorance of the innovativeness of creative accounting and manipulation of accounting principles. The purpose of this paper to guide the person who reads throughout the annual report, to make clear the financial statement prepared and to make him aware of the innovativeness of creative accounting that can arise by the manipulation of accounting principles.